Prevalence of Smoking Among Transgender Population Residing In Urban Chennai- A Cross Sectional Survey: Life Sciences-Dentistry Orthodontics - Shanmugam, Manikandan; Navaneethakrishnan, Kurunji Kumaran; Venkatachalam, Bhaskar; Kandasamy, Rajasigamani; Baalann, Krishna Prasanth (International Journal of Life Science and Pharma Research, 2022)
In general, there is a lack of research on the transgender population and tobacco use. Findings from previous studies are in conflict regarding the use of tobacco products among transgender populations. The purpose of this study was to estimate the prevalence of current tobacco use among transgender population in and around Chennai city. A cross sectional survey was conducted to assess the prevalence of smoking among transgender. A direct interview was conducted using questionnaire related to smoking and transgender type. Descriptive statistics was used to give the prevalence, socio demographic variables and chi square test was used to compare the smoking habit with socio demographic data. The prevalence of smoking among transgender was forty percentage. While comparing age group and smoking habit or type of transgender(male to female and female to male) and smoking there was no significant association observed(p value>0.05). Around 60% of them had the habit of Alcohol intake. While comparing education and occupation with smoking behavior, there was a strong significant association (p value 0.006, 0.002) found in this study. Cigarette was the most common type of tobacco used by these populations. Tobacco in the form of cigarette was common among Transgender population. Future research is needed with an increased sample size to assess the quantity of cigarette intake. The data from this study can be used as a preliminary report to inform best and promising practices for tobacco control and prevention for the transgender population.